CMET-16. A PHASE II TRIAL OF BEVACIZUMAB IN PATIENTS WITH RECURRENT SOLID TUMOR BRAIN METASTASES WHO HAVE PROGRESSED FOLLOWING WHOLE BRAIN RADIATION THERAPY (WBRT): FINAL RESULTS. (11th November 2019) - Kumthekar, Priya; Dixit, Karan; Grimm, Sean; Lukas, Rimas; Schwartz, Margaret; Helenowski, Irene; Sharp, Laura; Nelson, Valerie; Raizer, Jeffrey
Abstract: BACKGROUND: Brain metastases (BM) are the most common intracranial tumor with limited treatment options following the progression after WBRT. METHODS: This open label phase 2 study for patients have progressed following WBRT enrolled participants who received bevacizumab 10 mg/kg intravenously every two weeks until CNS disease progression (one cycle=4 weeks). The primary endpoint was objective radiographic tumor response as defined by modified Response Assessment in Neuro-oncology (RANO) criteria. Secondary endpoints included safety, progression free survival (PFS), time to response, duration of response, overall survival (OS), and quality of life (QOL) as measured by FACT-G and FACT-Br. RESULTS: A total of 27 patients were registered of which 24 were evaluable for ORR (3 came off study prior to first follow up MRI brain). Median age was 53 (range 27–73), median number of cycles was 5.5 (range 1–20) with a median follow up of 8.7 months (range 2.4–47.9mo). Of the 24 evaluable patients, 6 showed radiographic response (Partial response=6, stable disease=16, progressive disease=2, 81% (22/24) experienced clinical benefit). The 6 month PFS: 46% (95% CI: 25% - 67%) and median PFS was 5.3 months. Median OS was 9.5 months (95% confidence interval 6.3m – 15.0m). For the patients who completed sequential QOL assessments, there no decline in QOL seen secondary to treatment and there was a non statistically significant improvement seen in the FACT-Br questionnaire. Overall, treatment was well tolerated with 3 grade 3 adverse events seen: hypertension (n=3), headache (n=1) and thrombotic event (n=1). CONCLUSION: For this pretreated BM population with historically poor clinical outcome and survival, we showed disease response with bevacizumab therapy, drug tolerability and improved survival as compared to historical controls. While larger studies are needed to confirm, bevacizumab therapy could be a viable option for solid tumor BM patients who experience progression following WBRT.